2013
DOI: 10.4315/0362-028x.jfp-12-259
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Condensed Tannins from Canadian Prairie Forages for Anti–Escherichia coli O157:H7 with an Emphasis on Purple Prairie Clover (Dalea purpurea Vent)

Abstract: Tannins from forages grown (n = 10) on the Canadian prairie, as well as from Quebracho, Rhus semialata, and brown seaweed (Ascophyllum nodosum), were screened for anti-Escherichia coli O157:H7 activity against E. coli O157:H7 strain 3081 at a concentration of 400 μg/ml for each tannin type, except for brown seaweed, which was at 50 μg/ml. Growth of the bacteria was assessed by measuring the optical density at 600 nm over 24 h. Tannin from seaweed at a concentration of 50 μg/ml inhibited growth of strain 3081. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…McMahon et al (1999) reported that feeding 10 to 20% sainfoin (fresh and hay) along with alfalfa reduced frothy bloat by 45 to 93% in a 3‐yr study. In another 3‐yr study to compare incidence of bloat, ruminal fermentation, and feed intake of steers grazing alfalfa and mixed alfalfa–sainfoin pastures showed that inclusion of 35% sainfoin in mixed alfalfa–sainfoin pastures reduced but did not eliminate bloat (Wang et al, 2006). In a 3‐yr grazing study, Sottie et al (2014) observed that bloat incidence increased from 5 to 43 and from 1 to 48 when the percentage of sainfoin was reduced from 29 to 7% and from 28 to 5% in sainfoin–alfalfa mixture, respectively.…”
Section: Effects Of Condensed Tannins On Nutritive and Feeding Value mentioning
confidence: 99%
See 2 more Smart Citations
“…McMahon et al (1999) reported that feeding 10 to 20% sainfoin (fresh and hay) along with alfalfa reduced frothy bloat by 45 to 93% in a 3‐yr study. In another 3‐yr study to compare incidence of bloat, ruminal fermentation, and feed intake of steers grazing alfalfa and mixed alfalfa–sainfoin pastures showed that inclusion of 35% sainfoin in mixed alfalfa–sainfoin pastures reduced but did not eliminate bloat (Wang et al, 2006). In a 3‐yr grazing study, Sottie et al (2014) observed that bloat incidence increased from 5 to 43 and from 1 to 48 when the percentage of sainfoin was reduced from 29 to 7% and from 28 to 5% in sainfoin–alfalfa mixture, respectively.…”
Section: Effects Of Condensed Tannins On Nutritive and Feeding Value mentioning
confidence: 99%
“…Some of the observed advantages of feeding sainfoin to ruminants compared with other comparable legume forages such as alfalfa include improved organic matter (OM) and protein digestion, increased intestinal amino acids absorption and N retention, more efficient utilization of energy and protein, and enhanced growth. Probably the most significant feed‐related characteristic of sainfoin is its non‐bloating nature (Sottie et al, 2014; Wang et al, 2006). Sainfoin has also been reported to reduce parasites such as nematodes in the ruminant digestive tract (Hoste et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Purple prairie clover has been shown to possess high CT concentrations (up to 94 g/kg DM) throughout the year (Berard et al, 2011;Jin et al, 2012;Li et al, 2014). In vitro studies showed that among tannins isolated from forages common to western Canada, only PPC CT possessed strong anti-E. coli O157:H7 and anti-generic E. coli activity (Wang et al, 2013a), a toxicity that was linked to disruption of the bacterial cell membrane (Liu et al, 2013). Therefore, PPC offers promise as a forage for dietary mitigation of E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 98%
“…The inhibitory action of tannins on microbes occurs in cell membranes, through cell aggregation and disruption of membranes and cell function, in general tannins cause protein deposition, but tannin's anti-microbial activity is specific, according to the chemical composition and structure of tannins. Condensed tannins isolated from several plants have been shown to have strong activity against Gram-negative bacteria, including Salmonella, Shigella, Staphylococcus, Pseudomonas and Helicobacter pylori (Liu et al 2013;Wang et al 2013). Tannins are known to have anti-inflammatory, astringent, and antiseptic activities, they inhibit the enzyme systems of microorganisms, tannic acid inhibits phosphatidylcholine liposomes which damage microorganism membranes, is also able to bind iron that is needed by microorganisms, resulting in malfunctioning of aerobic microorganisms (Linarti et al 2011).…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%